Penilaian Pelaksanaan Pemeliharaan dan Perawatan Bangunan Hotel di Sleman Yogyakarta - Sely Novita Sari; Rizal Maulana; Anggi Hermawan; Oggi Heicqal Ardian (G-Tech: Jurnal Teknologi Terapan, 2024)
The government has issued guidelines based on Minister of Public Works Regulation NO.24/PRT/M/2008 for the maintenance and care of buildings. These guidelines aim to reduce damage and issues in building construction in terms of quality, facilities, and safety, and to facilitate handling if damage occurs. Structural observation of buildings requires careful testing. This study evaluates the maintenance and care of buildings in accordance with these regulations. The results show that, out of six hotels inspected, the implementation of building maintenance reached 55.57%, while the implementation of building care reached 63.39%. This study helps assess the extent to which these guidelines are applied and understood in the field.